2021
DOI: 10.21123/bsj.2021.18.4.1261
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Photodegradation of Congo Red Dye from Aqueous Solutions Using Bimetallic Au–Pd/TiO2 Photocatalyst

Abstract: In this study, the photodegradation of Congo red dye (CR) in aqueous solution was investigated using Au-Pd/TiO 2 as photocatalyst. The concentration of dye, dosage of photocatalyst, amount of H 2 O 2 , pH of the medium and temperature were examined to find the optimum values of these parameters. It has been found that 28 ppm was the best dye concentration. The optimum amount of photocatalyst was 0.09 g/75 mL of dye solution when the degradation percent was ~ 96 % after irradiation time of 12 hours, while the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thirty minutes after Sol was generated, the added graphene-supported material restrained the colloid formation. The pH of the solution was 1-3 and was controlled by adding hydrochloric acid with stirring settings 24 . After 60 minutes, the slurry was separated and then washed off with water, and then the resulting substance was dried at 120º C for 16 hours.…”
Section: Synthesis Of the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty minutes after Sol was generated, the added graphene-supported material restrained the colloid formation. The pH of the solution was 1-3 and was controlled by adding hydrochloric acid with stirring settings 24 . After 60 minutes, the slurry was separated and then washed off with water, and then the resulting substance was dried at 120º C for 16 hours.…”
Section: Synthesis Of the Catalystsmentioning
confidence: 99%
“…
10,11, and photodegradation [12][13][14] . It has been found that the photocatalytic degradation process is an interesting method because of its low cost, as well as because it
…”
mentioning
confidence: 99%